Semiquantitative theory for high-field low-temperature properties of a distorted diamond spin chain - Derzhko, O.; Richter, J.; Krupnitska, O. (Condensed Matter Physics, 2012)
We consider the antiferromagnetic Heisenberg model on a distorted diamond chain and use the localized-magnon picture adapted to a distorted geometry to discuss some of its high-field low-temperature properties. More specifically, in our study we assume that the partition function for a slightly distorted geometry has the same form as for ideal geometry, though with slightly dispersive one-magnon energies. We also discuss the relevance of such a description to azurite. Ми розглядаємо антиферомагнiтну модель Гайзенберга на деформованому ромбiчному ланцюжку i використовуємо картину локалiзованих магнонiв, пристосовану до деформованої геометрiї, щоб обговорити деякi низькотемпературнi властивостi моделi у сильних полях. Конкретнiше, у нашому дослiдженнi ми вважаємо, що статистична сума у випадку дещо деформованої геометрiї має таку ж форму як i у випадку iдеальної геометрiї, але з трошки дисперсними одномагнонними енергiями. Ми також обговорюємо застосовнiсть такого опису для азуриту.